Dispersion-enhanced admixture for architectural ceramic slurry as well as preparation method and application of dispersion-enhanced admixture
The ceramic slurry dispersion-enhanced admixture is prepared by combining modified silicate materials, carboxylic acid graft esteramine copolymers and modified polymethacrylates, and the dispersion and enhancement compatibility of ceramic slurry are solved. The problem of this paper improves the fluidity and mechanical strength of ceramics, reduces the energy consumption in the production process, and achieves high efficiency and environmental protection in ceramic production.
Patent Information
- Application Number
- CN202411563087.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-05
AI Technical Summary
It is difficult for existing ceramic admixtures to improve the dispersion and enhancement of ceramic slurry at the same time, resulting in insufficient compatibility of fluidity and mechanical properties in ceramic production. In addition, traditional admixtures often increase viscosity when used, affecting the fluidity of ceramics.
Using modified silicate materials, carboxylic acid graft esteramine copolymers and modified polymethacrylate salts, ceramic slurry dispersion-enhanced admixtures, etc., to improve the The fluidity and mechanical strength of the ceramic slurry are adjusted by charging shielding agent to enhance the dispersion effect of ceramic particles.
It realizes efficient dispersion and enhancement of ceramic slurry, reduces the energy consumption of ball milling and sintering processes, improves the strength and production efficiency of green bodies, and has the characteristics of green and environmental protection. It is suitable for a variety of ceramic raw materials and has wide applicability.
Smart Images

Figure BDA0005118447270000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic production additives, and specifically relates to a building ceramic slurry dispersion-enhancing additive and a preparation method and application thereof. Background Art
[0002] Ceramics is an inorganic non-metallic material prepared by high-temperature sintering. It is mainly composed of minerals such as clay, feldspar, and quartz. It has excellent properties such as high hardness, high temperature resistance, and corrosion resistance. It is widely used in the fields of structural materials and functional materials. With the development of materials science, modern ceramics are divided into traditional ceramics and new ceramics. Traditional ceramics include daily-use ceramics, architectural ceramics, etc.; new ceramics cover electronic ceramics, bioceramics, structural ceramics, etc., which play an important role in electronic components, medical devices, high temperature and high-intensity environments. The production process of ceramics usually includes raw material processing, molding, drying, sintering and surface treatment. The dispersibility and particle size of the raw materials directly affect the quality of the product. In order to improve the fluidity and processing performance of the slurry, admixtures are often added in the production to enhance the mechanical properties of the ceramics, increase the sintering density, and reduce defects. Among them, the role of the dispersant is to reduce the interaction force between particles, make the solid particles evenly distributed, improve the fluidity and stability of the slurry, ensure the smooth molding and sintering process, and effectively prevent the generation of cracks and defects. In addition, reducing the moisture content of the slurry entering the tower can also reduce the energy consumption of evaporating water in the drying process, which is of great significance to improving production efficiency and energy conservation and emission reduction. The reinforcing agent is mainly used to improve the mechanical strength and impact resistance of ceramics, increase the density and durability of the material, and make it perform better in high stress or harsh environments.
[0003] At present, commonly used architectural ceramic dispersants include inorganic electrolytes (such as sodium phosphate, sodium silicate, sodium carbonate, sodium metasilicate, etc.), organic small molecules (such as sodium citrate, sodium humate, etc.) and organic polymers (such as sodium polyacrylate, polyacrylamide, styrene-maleic anhydride copolymer, etc.). These dispersants exert dispersion mechanisms through electrostatic repulsion or (and) steric hindrance. Common architectural ceramic embryo body enhancers include sodium lignin sulfonate, calcium lignin sulfonate, sodium methyl cellulose, polyvinyl alcohol and propylene polymers, sodium polyacrylate and sodium alginate. The use of enhancers can improve the green body strength of the embryo, but it usually also increases the viscosity of the slurry, which has an adverse effect on the fluidity of the ceramic slurry. Therefore, how to maintain good fluidity of the slurry while improving the green body strength is a major challenge in the application of ceramic admixtures.
[0004] The above-mentioned traditional ceramic admixtures have limitations in terms of effectiveness, dosage and cost during use, and it is difficult to simultaneously meet the requirements for dispersibility and enhanced performance in ceramic production. Therefore, the research and development of multifunctional dispersants has gradually become a hot topic. For example, Chinese invention patent CN112573929A discloses a composite ceramic water reducer, whose main components include sodium metasilicate, sodium polyphosphate, methyl cellulose, sodium citrate, sodium perborate, magnesium carbonate, polyolamine, fatty alcohol polyoxyethylene ether and waste sand. The water reducer can not only reduce the moisture content of mud, shorten the ball milling time, and reduce the grinding power consumption, but also improve the strength of ceramic dry blanks, and has the functions of aiding grinding, enhancing strength and reducing water. The water reducer is suitable for clay containing more barren materials, can improve the forming qualification rate of products, reduce production costs, and has energy-saving and emission reduction effects. Chinese invention patent CN104291830A discloses a composite ceramic dispersant, which is mainly composed of sodium humate, polyacrylamide, sodium polyacrylate and potassium persulfate, and the preparation of the dispersant adopts microwave radiation technology, which significantly improves the reaction speed and efficiency. The dispersant can effectively improve the fluidity of ceramic slurry, reduce the water content of mud, thereby reducing drying energy consumption, and improving the strength of ceramic products. The dispersant has good versatility, is suitable for various clay mineral raw materials, and can still achieve good dispersion effect when added in a small amount. Chinese invention patent CN105968270A discloses a composite ceramic water reducer, which mainly includes tannin extract, bisallyl polyethylene glycol ether, acrylic acid glucose ester, unsaturated carboxylic acid and its salt, initiator and inorganic dispersant, and the above components are mixed and then subjected to polymerization reaction, and the temperature and reaction time are controlled to obtain a ceramic water reducer with good fluidity and viscosity control effect. The water reducing agent can reduce the water content in the ceramic slurry, improve the fluidity of the slurry and the flexural strength of the green body, thereby achieving the effects of energy saving and consumption reduction and improving the performance of ceramic products.
[0005] From the above, it can be seen that the composite ceramic water reducers / dispersants currently involved mainly combine inorganic or organic key functional groups to further improve the dispersibility of the synthesized or combined products in the ceramic slurry, thereby reducing the demand for water by the ceramic clay particles during ball milling. However, there are still relatively limited ceramic admixture products on the market that can have both good dispersibility and significantly enhance the strength of the green body. The market demand for composite ceramic admixtures is still large, and the characteristics of strong versatility, small dosage and good effect are proposed. Therefore, it is necessary to further develop multifunctional ceramic admixtures with comprehensive functions, small usage and green environmental protection. Summary of the invention
[0006] In order to overcome the deficiencies of the above-mentioned prior art, the present invention proposes a ceramic slurry dispersing-enhancing admixture and a preparation method thereof, aiming to solve the compatibility problem between the dispersibility and enhancement of ceramic slurry. The admixture can effectively improve the dispersibility and fluidity of ceramic slurry, and enhance the mechanical strength and durability of the final product, providing a more efficient and stable solution for ceramic production, and has practical application significance.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The present invention provides a ceramic slurry dispersing-enhancing admixture, wherein the raw materials of the admixture include 15-25 parts of modified silicate material, 3-8 parts of carboxylic acid grafted ester amine copolymer, 1-5 parts of modified polymethacrylate, and 6-12 parts of charge shielding agent in parts by mass;
[0009] The preparation method of the modified silicate material is as follows: adding a sodium hydroxide aqueous solution to water glass, adjusting the modulus thereof to 2.0, then adding an aluminum chloride solution and ore powder, and controlling the silicon-aluminum ratio in the solution to be 200:2-4, then calcining the mixed solution at a temperature of 625-700° C. for 5-25 minutes, and finally cooling and grinding to obtain the modified silicate material;
[0010] The carboxylic acid grafted esteramine copolymer is an alcoholamine-carboxylic acid type polymer. The preparation method thereof is as follows: 59-66 parts of N-methyl mixed alcoholamine, 33-39 parts of maleic anhydride, 1-1.6 parts of concentrated sulfuric acid, 15-100 parts of butyl acetate and 0.4-0.6 parts of hydroquinone are mixed, reacted at a temperature of 110-120° C. for 4-8 hours, distilled under reduced pressure and unreacted raw materials are recovered, separated and purified to obtain an intermediate, then the intermediate is diluted with water to a mass concentration of 15%-30%, heated to 80-90° C., and then 40%-50% of isopentanol polyoxyethylene ether and 5%-10% of potassium persulfate are added, reacted for 2-4 hours, cooled, and the pH of the solution is adjusted to neutral to obtain the carboxylic acid grafted esteramine copolymer;
[0011] The preparation method of the modified polymethacrylate comprises the following steps: 92-105 parts of an acrylic acid solution with a mass concentration of 10% are mixed with 40-70 parts of sodium methacrylate, and nitrogen is replaced for 15-30 minutes under continuous stirring, and then 7.5-10 parts of potassium persulfate and 3.8-5.1 parts of sodium bisulfite redox initiator are added, and then the mixture is heated to 60-80° C. to initiate a polymerization reaction for 1-3 hours, and then 0.2-0.8 parts of hydroxyethyl cellulose is added to the reaction solution and the reaction is maintained at a constant temperature for 2-4 hours, and after the reaction, the modified polymethacrylate is obtained by separation and purification.
[0012] The present invention prepares a new type of layered silicate by utilizing the specific dehydration reaction and decomposition reaction of water glass under medium temperature conditions. The raw material has a strong ion exchange capacity, can enhance the water-reducing effect of traditional phosphate dispersants, further improve the fluidity of ceramic slurry, and has the effect of pH alkalinity adjustment and enhancing green body strength. Subsequently, a carboxylic acid grafted ester amine copolymer is prepared by chemical synthesis. The polymer plays a grinding aid role in the mixing of ceramic raw materials and a water-reducing role in the slurry, and has the effect of maintaining the stability of the ceramic slurry and delaying the stratification time of the ceramic slurry when it is standing. The ceramic slurry admixture prepared by this formula has a multifunctional effect, a wide range of applicability to the types of ceramic raw materials, a good dispersing effect on the slurry, and the water demand can be further reduced, which is conducive to energy saving and consumption reduction in the production process. It is a green and environmentally friendly high-performance admixture.
[0013] Preferably, the mineral powder includes at least one of montmorillonite powder, vermiculite powder, hydrotalcite powder and barite powder.
[0014] Preferably, the particle size of the ore powder is less than 0.1 mm, and its mass fraction in the mixed liquid is 10%-20%.
[0015] Preferably, the monomer molecular weight of the isopentenol polyoxyethylene ether is 800-1600.
[0016] Preferably, isopentanol polyoxyethylene ether with a mass concentration of 40%-50% and potassium persulfate with a mass concentration of 5%-10% are slowly added dropwise within 5 hours.
[0017] Preferably, the oxidation initiator is potassium persulfate, and the reduction initiator is sodium bisulfite.
[0018] Preferably, the charge shielding agent is at least one of sodium hexametaphosphate, sodium tripolyphosphate, sodium polyacrylate, sodium polycarboxylate, sodium citrate, sodium oxalate and sodium humate.
[0019] The present invention also provides the use of the ceramic slurry dispersing-enhancing additive in the preparation of architectural ceramics.
[0020] The ceramic slurry additive of the present invention not only satisfies the dispersibility of the ceramic slurry, but also optimizes the green body strength in the subsequent embryo making process, ensuring the performance of the product in energy saving and consumption reduction and efficient production. It can meet the ceramic industry's demand for efficient and low-energy production processes, and at the same time promote the improvement of ceramic product quality and production efficiency.
[0021] Preferably, the ceramic slurry dispersing-enhancing admixture is added in an amount of 0.1-1.2 wt % when preparing architectural ceramics.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention discloses a ceramic slurry dispersing-enhancing admixture, the raw materials of which include modified silicate material, carboxylic acid grafted ester amine copolymer, modified polymethacrylate and charge shielding agent. The ceramic slurry dispersing-enhancing admixture of the present invention is applied to the ball milling dispersion and sintering process of ceramic production, which can further improve the dispersion performance of the ceramic slurry, reduce the water demand of the ball milling process and the energy consumption of the subsequent sintering process, and can improve the green body strength, which is beneficial to the subsequent processing stability, and reduces the scrap rate, thereby improving the ceramic production efficiency. In general, the present invention has the following advantages:
[0024] (1) The ceramic multifunctional admixture provided by the present invention has a small amount of addition, loose storage conditions, meets environmental protection requirements, and is suitable for large-scale production conditions. From the perspective of product function, the admixture integrates multiple functions such as grinding aid, dispersion and water reduction, alkaline pH buffering, stable suspended colloids and enhanced embryo strength. It not only ensures the flow quality of the slurry and the strength of the green body during the ceramic production process, but also helps the production process to reduce the water demand in the material preparation process and the energy consumption of the subsequent spray drying process. It is green and environmentally friendly and is a multifunctional admixture.
[0025] (2) In the ceramic multifunctional admixture raw material provided by the present invention, the use of modified silicate material greatly reduces the dosage of phosphate dispersants commonly used in ceramic processes, and reduces the environmental impact of traditional admixtures. The modified silicate material has a certain grinding aid effect and high temperature stability, which can ensure that the effect continues to be exerted during the ball milling heating process, which is conducive to shortening the ball milling process of the ceramic raw material and optimizing the particle grading. In the ceramic slurry, the modified silicate material has pH buffering capacity and strong cation exchange capacity. On the one hand, it can stabilize the alkaline environment of the ceramic slurry so that the surface of the ceramic particles is as negatively charged as possible. On the other hand, the unique layered structure of the modified silicate material has negatively charged siloxy groups that attract calcium ions, magnesium ions and aluminum ions in the slurry into the interlayer through electrical neutralization, so that the negative charge on the surface of the ceramic particles is further increased, thereby enhancing the dispersion effect. This modified silicate material can also react chemically with other ceramic raw materials during the subsequent embryo sintering process, and the new phase structure formed forms a bridging or filling effect inside the material, thereby enhancing the overall mechanical strength of the ceramic material.
[0026] (3) The ceramic multifunctional admixture raw material provided by the present invention uses modified polymethacrylate, which is a linear polycarboxylic acid dispersant. The main chain has strong anionic characteristics, which can attract and stabilize positively charged particles. The side chains have a large number of hydroxyl groups and have good water solubility and adhesion. Based on its molecular characteristics, the carboxyl and sulfonate groups on the main chain can provide negative charges for ceramic particles, enhance the electrostatic repulsion between particles, and prevent particle agglomeration. The grafted side chains provide steric hindrance to further prevent particles from approaching and agglomerating, maintain a good dispersion state of particles, and have a certain stability to temperature and pH changes, which is conducive to the formation of a stable dispersion system of slurry under different conditions.
[0027] (4) The ceramic multifunctional admixture raw material provided by the present invention uses a carboxylic acid grafted esteramine copolymer. This polymer has a comb-shaped molecular structure of the carboxylic acid series, and functional groups such as polyoxyethylene chains, hydroxyl groups, amine groups, carboxyl groups, and ester groups are distributed on the molecular side chains, which is conducive to the active part of the molecular surface contacting with the surface of ceramic particles to form an adsorption film, and the molecular side chains can form a three-dimensional intersection with the side chains on the surface of other particles, reducing direct contact between particles, playing an excellent grinding aid and dispersion role, and further optimizing the particle grading effect of the ceramic raw material after ball milling. In addition, the active sites on the molecules can undergo cross-linking reactions with metal cations to form a three-dimensional gel network structure, capture and fix suspended ceramic particles, prevent them from settling, maintain the stability of suspended particles under static or low shear stress, and increase embryo production efficiency. DETAILED DESCRIPTION
[0028] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0029] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0030] The units (parts) involved in the following examples are all parts by mass.
[0031] Example 1
[0032] A ceramic slurry dispersing-enhancing additive, whose raw materials are, by weight, 18.7 parts of modified silicate material, 4.7 parts of carboxylic acid grafted ester amine copolymer, 3.5 parts of modified polymethacrylate, and 8 parts of charge shielding agent (sodium hexametaphosphate).
[0033] The preparation method is as follows: the various raw materials mentioned above are mixed according to the proportions. The preparation of the modified silicate material, the carboxylic acid grafted ester amine copolymer and the modified polymethacrylate is as follows:
[0034] The preparation method of the modified silicate material is as follows: take 100 parts of water glass with a modulus of 2.4 and a solid content of 49 produced industrially, add 25.33 parts of a sodium hydroxide solution with a mass concentration of 15% prepared by deionized water, then add 5.87 parts of an aluminum chloride solution with a mass concentration of 10% and 17 parts of montmorillonite powder (particle size less than 0.1 mm), adjust the modulus of the water glass to 2.0 (silicon-aluminum ratio in the solution = 200:3), then place the water glass with the adjusted modulus in a rotary stirring furnace, set a heating rate of 30°C / min, heat to a heat preservation temperature of 675°C, and keep warm for 9 minutes. After the heat preservation is completed, use an insulation tool to take out the crucible, quickly cool the product to room temperature through cold air, and obtain the modified silicate material after crushing and grinding.
[0035] The preparation method of the carboxylic acid grafted ester amine copolymer is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 50 parts of N-methyldiethanolamine, 41.2 parts of maleic anhydride, 1.3 parts of 98% concentrated sulfuric acid, 41.2 parts of butyl acetate, and 0.5 parts of hydroquinone are added in sequence, the temperature is raised to 115° C. and stirred continuously, after reacting for 6 hours, butyl acetate and unreacted raw materials are recovered by reduced pressure distillation (vacuum degree 200-300 mmHg, 60-80° C.), and purified (water phase extraction method) ) to obtain an intermediate; then take 8.4 parts of the intermediate and dilute it with 45 parts of deionized water to a concentration of 15.7%, add it to a reaction container, keep the temperature at 85±1°C, and then slowly drop 15 parts of 5.5% ammonium persulfate initiator solution and 60.1 parts of 50% isopentanol polyoxyethylene ether (monomer molecular weight is 1200) solution within 5 hours, keep it for 3 hours, cool the product to below 40°C, and adjust it to neutral with 30% NaOH solution, and finally obtain an orange-yellow or orange-red carboxylic acid grafted ester amine copolymer liquid.
[0036] The preparation method of the modified polymethacrylate is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 73 parts of a 10% mass concentration acrylic acid solution and 47 parts of sodium methacrylate sulfonate are added, and nitrogen is replaced for about 20 minutes under continuous stirring, and then 6.1 parts of potassium persulfate and 3.04 parts of sodium bisulfite redox initiator are added in sequence, and the polymerization reaction is initiated at 70° C. for 2 hours, and then 0.3 parts of hydroxyethyl cellulose is slowly added to the reaction solution, and the reaction is kept at a constant temperature for 3 hours. After the reaction is complete, the modified polymethacrylate is obtained after separation and purification.
[0037] Example 2
[0038] A ceramic slurry dispersing-enhancing additive, whose raw materials are, by weight, 17.0 parts of modified silicate material, 4.9 parts of carboxylic acid grafted ester amine copolymer, 2.8 parts of modified polymethacrylate, and 7 parts of charge shielding agent (sodium hexametaphosphate).
[0039] The preparation method is as follows: the various raw materials mentioned above are mixed according to the proportions. The preparation of the modified silicate material, the carboxylic acid grafted ester amine copolymer and the modified polymethacrylate is as follows:
[0040] The preparation method of the modified silicate material is as follows: take 100 parts of water glass with a modulus of 2.4 and a solid content of 49 produced industrially, add 25.33 parts of a sodium hydroxide solution with a mass concentration of 15% prepared by deionized water, then add 5.87 parts of an aluminum chloride solution with a mass concentration of 10% and 17 parts of montmorillonite powder (particle size less than 0.1 mm), adjust the modulus of the water glass to 2.0 (silicon-aluminum ratio in the solution = 200:3), then place the water glass with the adjusted modulus in a rotary stirring furnace, set a heating rate of 30°C / min, heat to a heat preservation temperature of 675°C, and keep warm for 9 minutes. After the heat preservation is completed, use an insulation tool to take out the crucible, quickly cool the product to room temperature through cold air, and obtain the modified silicate material after crushing and grinding.
[0041] The preparation method of the carboxylic acid grafted ester amine copolymer is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 47 parts of N-methyldiethanolamine, 38.2 parts of maleic anhydride, 1.5 parts of 98% concentrated sulfuric acid, 38.2 parts of butyl acetate, and 0.54 parts of hydroquinone are added in sequence, the temperature is raised to 115° C. and stirred continuously, after reacting for 6 hours, butyl acetate and unreacted raw materials are recovered by reduced pressure distillation (vacuum degree 200-300 mmHg, 60-80° C.), and purified (water phase extraction method) The intermediate is obtained; then 15.9 parts of the intermediate is diluted with 67.6 parts of deionized water to a concentration of 19%, added to a reaction vessel, the temperature is maintained at 85±1°C, and then 24.4 parts of a 6.6% ammonium persulfate initiator solution and 87.5 parts of a 48.3% isopentanol polyoxyethylene ether (monomer molecular weight is 1200) solution are slowly added dropwise within 5 hours, and after maintaining for 3 hours, the product is cooled to below 40°C, and adjusted to neutral with a 30% NaOH solution, and finally an orange-yellow or orange-red alcoholamine-carboxylic acid polymer liquid is obtained.
[0042] The preparation method of the modified polymethacrylate is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 87 parts of a 10% mass concentration acrylic acid solution and 47.9 parts of sodium methacrylate sulfonate are added, and nitrogen is replaced for about 20 minutes under continuous stirring, and then 7.66 parts of potassium persulfate and 3.8 parts of sodium bisulfite redox initiator are added in sequence, and the polymerization reaction is initiated at 70° C. for 2 hours, and then 0.44 parts of hydroxyethyl cellulose is slowly added to the reaction solution, and the reaction is kept at a constant temperature for 3 hours. After the reaction is complete, the modified polymethacrylate is obtained after separation and purification.
[0043] Example 3
[0044] A ceramic slurry dispersing-enhancing additive, whose raw materials are, by weight, 20 parts of modified silicate material, 5.5 parts of carboxylic acid grafted ester amine copolymer, 3.0 parts of modified polymethacrylate, and 10 parts of charge shielding agent (sodium hexametaphosphate).
[0045] The preparation method is as follows: the various raw materials mentioned above are mixed according to the proportions. The preparation of the modified silicate material, the carboxylic acid grafted ester amine copolymer and the modified polymethacrylate is as follows:
[0046] The preparation method of the modified silicate material is as follows: take 100 parts of water glass with a modulus of 2.4 and a solid content of 49 produced industrially, add 25.33 parts of a sodium hydroxide solution with a mass concentration of 15% prepared by deionized water, then add 5.87 parts of a 10% mass concentration aluminum chloride solution and 17 parts of montmorillonite powder (particle size less than 0.1 mm), adjust the modulus of the water glass to 2.0 (silicon-aluminum ratio in the solution = 200:3), then place the water glass with the adjusted modulus in a rotary stirring furnace, set a heating rate of 30°C / min, heat to a heat preservation temperature of 675°C, and keep warm for 9 minutes. After the heat preservation is completed, use an insulation tool to take out the crucible, quickly cool the product to room temperature through cold air, and obtain the modified silicate material after crushing and grinding.
[0047] The preparation method of the carboxylic acid grafted ester amine copolymer is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 51 parts of N-methyldiethanolamine, 41.7 parts of maleic anhydride, 1.5 parts of 98% concentrated sulfuric acid, 41.7 parts of butyl acetate, and 0.5 parts of hydroquinone are added in sequence, the temperature is raised to 115° C. and stirred continuously, after reacting for 6 hours, butyl acetate and unreacted raw materials are recovered by reduced pressure distillation (vacuum degree 200-300 mmHg, 60-80° C.), and purified (water phase extraction method) to obtain intermediate; then take 9.1 parts of the intermediate and dilute it with 37.1 parts of deionized water to a concentration of 19.6%, add it to a reaction container, keep the temperature at 85±1°C, and then slowly drop 12.0 parts of 6.5% ammonium persulfate initiator solution and 42.8 parts of 47.7% isopentanol polyoxyethylene ether (monomer molecular weight is 1200) solution within 5 hours. After keeping for 3 hours, the product is cooled to below 40°C and adjusted to neutral with 30% NaOH solution to finally obtain an orange-yellow or orange-red alcoholamine-carboxylic acid polymer liquid.
[0048] The preparation method of the modified polymethacrylate is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 85 parts of a 10% mass concentration acrylic acid solution and 51 parts of sodium methacrylate sulfonate are added, and nitrogen is replaced for about 20 minutes under continuous stirring, and then 7.65 parts of potassium persulfate and 3.8 parts of sodium bisulfite redox initiator are added in sequence, and the polymerization reaction is initiated at 70° C. for 2 hours, and then 0.34 parts of hydroxyethyl cellulose is slowly added to the reaction solution, and the reaction is kept at a constant temperature for 3 hours. After the reaction is complete, the modified polymethacrylate is obtained after separation and purification.
[0049] Example 4
[0050] A ceramic slurry dispersing-enhancing additive, whose raw materials are, by weight, 23 parts of modified silicate material, 5.1 parts of carboxylic acid grafted ester amine copolymer, 3.2 parts of modified polymethacrylate, and 8.5 parts of charge shielding agent (sodium hexametaphosphate).
[0051] The preparation method is as follows: the various raw materials mentioned above are mixed according to the proportions. The preparation of the modified silicate material, the carboxylic acid grafted ester amine copolymer and the modified polymethacrylate is as follows:
[0052] The preparation method of the modified silicate material is as follows: take 100 parts of water glass with a modulus of 2.4 and a solid content of 49 produced industrially, add 25.33 parts of a sodium hydroxide solution with a mass concentration of 15% prepared by deionized water, then add 5.87 parts of a 10% mass concentration aluminum chloride solution and 17 parts of montmorillonite powder (particle size less than 0.1 mm), adjust the modulus of the water glass to 2.0 (silicon-aluminum ratio in the solution = 200:3), then place the water glass with the adjusted modulus in a rotary stirring furnace, set a heating rate of 30°C / min, heat to a heat preservation temperature of 675°C, and keep warm for 9 minutes. After the heat preservation is completed, use an insulation tool to take out the crucible, quickly cool the product to room temperature through cold air, and obtain the modified silicate material after crushing and grinding.
[0053] The preparation method of the carboxylic acid grafted ester amine copolymer is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 58 parts of N-methyldiethanolamine, 48.2 parts of maleic anhydride, 2.1 parts of 98% concentrated sulfuric acid, 47.6 parts of butyl acetate, and 0.5 parts of hydroquinone are added in sequence, the temperature is raised to 115° C. and stirred continuously, after reacting for 6 hours, butyl acetate and unreacted raw materials are recovered by reduced pressure distillation (vacuum degree 200-300 mmHg, 60-80° C.), and the medium is purified (water phase extraction method) to obtain intermediate; then take 14.3 parts of the intermediate and dilute it with 61.3 parts of deionized water to a concentration of 22.3%, add it to the reaction vessel, keep the temperature at 85±1°C, and then slowly add 19.9 parts of 6.9% ammonium persulfate initiator solution and 68.4 parts of 45.7% isopentanol polyoxyethylene ether (monomer molecular weight is 1200) solution dropwise within 5 hours, keep for 3 hours, cool the product to below 40°C, and adjust it to neutral with 30% NaOH solution, and finally obtain an orange-yellow or orange-red alcoholamine-carboxylic acid polymer liquid.
[0054] The preparation method of the modified polymethacrylate is as follows: in a four-necked flask equipped with a constant temperature oil bath, a thermometer, a stirrer and a condenser, 76 parts of a 10% mass concentration acrylic acid solution and 43.3 parts of sodium methacrylate sulfonate are added, and nitrogen is replaced for about 20 minutes under continuous stirring, and then 7.6 parts of potassium persulfate and 3.8 parts of sodium bisulfite redox initiator are added in sequence, and the polymerization reaction is initiated at 70° C. for 2 hours, and then 0.25 parts of hydroxyethyl cellulose is slowly added to the reaction solution and the reaction is maintained at a constant temperature for 3 hours. After the reaction is complete, the modified polymethacrylate is obtained after separation and purification.
[0055] Experimental example: performance test
[0056] The main components of the ceramic formula used in this test are: kaolin (22%), clay (15%), bauxite (36%), stone (5%), and white sand (22%). Among them, the group to which the ceramic slurry dispersion-enhancing admixtures of Examples 1-4 were added was the experimental group (respectively recorded as Examples 1-4), and the group without any ceramic admixture (recorded as Comparative Example 1) and adding commercially available ceramic admixtures (recorded as Comparative Example 2, the main components include triethanolamine diluent with a mass concentration of 1.5% to 2%, sodium polyacrylate polymer solution with a mass concentration of 25% to 30%, sodium tripolyphosphate and water glass, prepared in a mass ratio of 5:3:1.5:0.5) were used as controls. Then the following tests were carried out:
[0057] (1) Flow properties of ceramic slurry
[0058] Fluidity refers to the ability of a slurry to flow under certain conditions, and is usually related to the viscosity of the slurry. The Tu-4 viscometer is used to measure the fluidity of each ceramic slurry to evaluate the rheological properties of the slurry. The Tu-4 viscometer indirectly reflects the viscosity of the slurry by measuring the time required for the slurry to flow out a specific volume. Viscosity is a key indicator of slurry fluidity. The higher the viscosity, the worse the fluidity; the lower the viscosity, the better the fluidity. By measuring fluidity, it is also possible to monitor whether stratification, precipitation or agglomeration of the slurry has occurred during storage or transportation.
[0059] At the standard temperature (25°C), weigh the ceramic formula material, control the water content at 28%, add 0.4% of the additive, and then mix it in a ball mill. Set the speed to 400r / min and ball mill for 15 minutes to obtain ceramic slurry; after the ball mill stops, quickly pour out the slurry, let it stand for 30s, and then fill the Tu-4 viscometer with the slurry until it overflows, ensuring that the liquid surface is flat and free of bubbles. Use a scraper to scrape off the excess sample at the mouth of the cup so that the liquid surface is flush with the mouth of the cup. Open the outflow port of the Tu-4 viscometer and start the stopwatch at the same time to observe the outflow of the liquid. Start timing from the stopwatch until the moment when the liquid flow is interrupted or a continuous interruption occurs. Stop timing. Each group was measured three times and the average value was taken. 0.5 As an indicator of fluidity.
[0060] Thickening reflects the change in rheological properties of the slurry during the static process due to particle interaction, flocculation and coagulation. Thickening is an important indicator for evaluating the stability and operability of the slurry under static conditions. The thixotropy of the slurry is quantitatively characterized by measuring the outflow time of the slurry after different static times (30s and 30min) after ball milling. Using ceramic slurry that has been static for 30min, the 30s flowability t 0.5 In the same way, a 30-min fluidity test was performed to obtain t 30 , and then calculate the thickness. Thickness = (t 30 / t0.5 ).
[0061] According to the test results in Table 1, the 30s ceramic slurry flow rate obtained by adding ceramic admixtures in Examples 1-4 is less than that in Comparative Example 2. Comparative Example 1 is the result of ball milling of ceramic formula materials without any admixtures. Without the action of admixtures, the ceramic formula soil is severely agglomerated after ball milling, and all water is adsorbed and wrapped by soil particles under the multiple influences of hydrophilic functional groups of soil particles, capillary water bridges and particle agglomeration and flocculation, so it does not have any fluidity. Further, under the action of the preferred admixture formula, the ceramic slurry presents a flowing state, and the admixtures of Examples 1-4 have significant advantages in the dispersion effect of ceramic slurry. After 30min, the focus is on evaluating the properties of the slurry flowing again after standing. Excessive thickening will affect the uniformity and fluidity of the slurry, which is not conducive to subsequent production processes and product quality. Under the condition of meeting production requirements, the 30min flow rate of Examples 1-4 is less than that of Comparative Example 2, and has a smaller degree of thickening. After standing for 1 day, the slurry did not show any stratification, indicating that the colloid stability was good.
[0062] Table 1 Flow properties test results
[0063] Group 30s flow rate 30min flow rate Thickness Example 1 37 45 1.216 Example 2 36 43 1.194 Example 3 33 39 1.182 Example 4 34 41 1.206 Comparative Example 1 Unable to flow Unable to flow / Comparative Example 2 43 55 1.279
[0064] (2) Green strength of ceramic slurry after drying
[0065] The green body strength is tested by dry pressing method: the prepared ceramic slurry is placed in a container, placed in a drying oven at 105°C and dried to a moisture content of 1-3%, then the dry powder is taken out, the powder is granulated, excess water is removed to make it reach a suitable moisture content (usually between 5-10%), and then passed through a 20-mesh sieve; the sieved ceramic particles are placed in a bag with good air permeability and aged for 24 hours to gradually evenly distribute the moisture and additives inside the particles; the aged powder is placed in a dry pressing mold, and a dry pressing molding machine is used to apply high pressure, the pressure is controlled to 30MPa, the pressure holding time is 10s, and the powder is pressed into a molded body; after the pressing is completed, the molded body is carefully taken out of the mold and placed in a drying oven, the temperature and humidity are controlled, the drying process is accelerated, and the moisture in the body is ensured to be completely evaporated, and the drying temperature is set to 115°C; finally, the green body flexural strength is tested according to the standard (GB / T 3810.4-2006).
[0066] It can be seen from the test results of Table 2 that the use of the dispersion-enhanced admixtures of Examples 1-4 significantly improves the green body flexural strength of the ceramic slurry. Among them, the admixture of the present invention is added to the ceramic slurry, which improves the fluidity, adjusts the water distribution in the slurry, makes the drying process more uniform, reduces local stress concentration, and prevents cracking and deformation during the drying process; the flaky structure of the modified silicate can fill the gaps between the ceramic particles, increase the density and uniformity of the green body, and this filling effect helps to reduce the pores and defects in the green body, improve the strength of the green body, and cooperate with the high molecular polymer to form a stable microscopic network structure inside the green body, providing additional reinforcement effects, helping to optimize the ceramic production process, and improve product quality and production efficiency.
[0067] Table 2 Green body flexural strength test results
[0068]
[0069] In summary, applying the ceramic slurry dispersing-enhancing admixture of the present invention to the ball milling dispersion and sintering links of ceramic production can further improve the dispersion performance of the ceramic slurry, reduce the water demand of the ball milling process and the energy consumption of the subsequent sintering process, and can improve the strength of the green body, which is beneficial to the subsequent processing stability, and reduce the scrap rate, thereby improving the ceramic production efficiency.
[0070] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A ceramic slurry dispersing-enhancing admixture, characterized in that: The raw materials of the additive include 15-25 parts of modified silicate material, 3-8 parts of carboxylic acid grafted ester amine copolymer, 1-5 parts of modified polymethacrylate, and 6-12 parts of charge shielding agent by weight. The preparation method of the modified silicate material is as follows: adding a sodium hydroxide aqueous solution to water glass, adjusting the modulus thereof to 2.0, then adding an aluminum chloride solution and ore powder, and controlling the silicon-aluminum ratio in the solution to be 200:2-4, then calcining the mixed solution at a temperature of 625-700° C. for 5-25 minutes, and finally cooling and grinding to obtain the modified silicate material; The carboxylic acid grafted esteramine copolymer is an alcoholamine-carboxylic acid type polymer. The preparation method thereof is as follows: 59-66 parts of N-methyl mixed alcoholamine, 33-39 parts of maleic anhydride, 1-1.6 parts of concentrated sulfuric acid, 15-100 parts of butyl acetate and 0.4-0.6 parts of hydroquinone are mixed, reacted at a temperature of 110-120° C. for 4-8 hours, distilled under reduced pressure and unreacted raw materials are recovered, separated and purified to obtain an intermediate, then the intermediate is diluted with water to a mass concentration of 15%-30%, heated to 80-90° C., and then 40%-50% of isopentanol polyoxyethylene ether and 5%-10% of ammonium persulfate are added, reacted for 2-4 hours, cooled, and the pH of the solution is adjusted to neutral to obtain the carboxylic acid grafted esteramine copolymer; The preparation method of the modified polymethacrylate comprises the following steps: 92-105 parts of an acrylic acid solution with a mass concentration of 10% are mixed with 40-70 parts of sodium methacrylate, and nitrogen is replaced for 15-30 minutes under continuous stirring, and then 7.5-10 parts of potassium persulfate and 3.8-5.1 parts of sodium bisulfite redox initiator are added, and then the mixture is heated to 60-80° C. to initiate a polymerization reaction for 1-3 hours, and then 0.2-0.8 parts of hydroxyethyl cellulose is added to the reaction solution and the reaction is maintained at a constant temperature for 2-4 hours, and after the reaction, the modified polymethacrylate is obtained by separation and purification.
2. A ceramic slurry dispersing-enhancing admixture according to claim 1, characterized in that: The mineral powder includes at least one of montmorillonite powder, vermiculite powder, hydrotalcite powder and barite powder.
3. A ceramic slurry dispersing-enhancing admixture according to claim 1, characterized in that: The particle size of the ore powder is less than 0.1 mm, and the mass fraction of the ore powder in the mixed liquid is 10%-20%.
4. A ceramic slurry dispersing-enhancing admixture according to claim 1, characterized in that: The monomer molecular weight of the isopentanol polyoxyethylene ether is 800-1600.
5. The ceramic slurry dispersing-enhancing admixture according to claim 1, characterized in that: Slowly drop isopentanol polyoxyethylene ether with a mass concentration of 40%-50% and potassium persulfate with a mass concentration of 5%-10% within 5 hours.
6. The ceramic slurry dispersing-enhancing admixture according to claim 1, characterized in that: The oxidation initiator is potassium persulfate, and the reduction initiator is sodium bisulfite.
7. The ceramic slurry dispersing-enhancing admixture according to claim 1, characterized in that: The charge shielding agent is at least one of sodium hexametaphosphate, sodium tripolyphosphate, sodium polyacrylate, sodium polycarboxylate, sodium citrate, sodium oxalate and sodium humate.
8. Use of the ceramic slurry dispersing-enhancing admixture according to any one of claims 1 to 7 in the preparation of architectural ceramics.
9. The use according to claim 8, characterized in that: The ceramic slurry dispersing-enhancing admixture is added in an amount of 0.1-1.2 wt % when preparing architectural ceramics.
Citation Information
Patent Citations
manufacture of ceramic bodies and composite products based on fibrous or powdery materials linked by silicate binders
BE768454A
Method for preparing porous desert greening brick
CN101386502A
Alcohol amine-carboxylic acid polymer as well as preparation method and application thereof
CN103193936A
Method for preparing thinned ceramic additive from garbage leachate
CN106747482A
Ceramic body reinforcing agent and preparation method thereof
CN115724669A
Cited By
Low-sensitivity admixture for small-slump concrete and preparation method of low-sensitivity admixture
CN120058263A